Exposure to solar ultraviolet radiation establishes a novel immune suppressive lipidome in skin-draining lymph nodes - Tse, Benita C. Y.; Ferguson, Angela L.; Koay, Yen Chin; Grau, Georges E.; Don, Anthony S.; Byrne, Scott N. (Frontiers in Immunology, 2023)
The ability of ultraviolet radiation to suppress the immune system is thought to be central to both its beneficial (protection from autoimmunity) and detrimental (carcinogenic) effects. Previous work revealed a key role for lipids particularly platelet activating factor and sphingosine-1-phosphate in mediating UV induced immune suppression. We therefore hypothesised that there may be other UV induced lipids that have immune regulatory roles. To assess this, mice were exposed to an immune suppressive dose of solar simulated UV (8 J/cm2). Lipidomic analysis identified 6 lipids (2 acylcarnitines, 2 neutral lipids, and 2 phospholipids) with significantly increased levels in the skin-draining lymph nodes of UV irradiated mice. Imaging mass spectrometry of the lipids in combination with imaging mass cytometry identification of lymph node cell subsets indicated a preferential location of UV-induced lipids to T cell areas. In vitro co-culture of skin-draining lymph node lipids with lymphocytes showed that lipid derived from UV-exposed mice have no effect on T cell activation but significantly inhibited T cell proliferation, indicating that the lipids play an immune regulatory role. These studies are important first steps in identifying novel lipids that contribute to UV mediated immune suppression.